SYNTHESIS OF 1D ZrO2 NANOMATERIALS FROM LOCAL ZrSiO4-BASED Zr(OH)4 PRECURSORS THROUGH A PRECURSOR-TEMPLATING METHOD - Septawendar, Rifki
One-dimensional zirconia nanomaterial is a promising material for many applications, such as for sensors, in catalysis, and as a reinforcing element in composites. This is due to its high aspect ratio, exhibiting an active and high specific surface area and high porosity, and showing high mechanical strength and high fracture toughness. One-dimensional zirconia nanomaterial is hardly found neither in a local nor international markets. However, many methods have been developed on the synthesis of one-dimensional zirconia material. The methods used soluble salts and organometallic compounds as the precursors and alcohol-based solvents, required specific instruments, and needed high energy. Thus, the methods are less economic to be applied on a large scale in Indonesia at this time. Considering Indonesia has a large deposit of zirconium silicates and the applications of one-dimensional zirconia nanomaterial in many industrial fields, the study on the synthesis of one-dimensional zirconia nanomaterial from zirconium silicates with a relative simple method is highly recommended. In this dissertation’s work, a method on the synthesis of zirconium silicate-based one-dimensional zirconia nanomaterials has been developed, namely a precursortemplating method. The method basically was a synthesis method of onedimensional zirconia nanomaterial using zirconium silicate-based zirconium hydroxide precursors assisted by one-dimensional directing organic templates that exhibit the hydroxyl groups (????????????????) and or the ethoxy groups (???????????? ????) and followed by calcination. The applied one-dimensional directing templates were ethylene glycol, poly ethylene glycol 6000, and natural polymers such as nano celluloses. All the templates comprise of the hydroxyl groups (????????????????) and or the ethoxy groups (???????????? ????), having ability to interact with the zirconium hydroxide precursors and to modify the zirconia in one-dimension nanostructures. Meanwhile, the zirconium hydroxide precursors were synthesized from zirconium silicates via a sodium carbonate-destruction method. The method is essentially the decomposition of zirconium silicates by sodium carbonates at a high temperature, resulting in a water soluble sodium silicate compound and an acid soluble sodium zirconate compound; and then followed by slow hydrolysis of the zirconium salts, giving rise to zirconium hydroxide precursors. This study aims to synthesize one-dimensional zirconia nanomaterials from the technical grade local zirconium silicate-based zirconium hydroxide precursors through a precursor-templating method. Synthesis of one-dimensional zirconia nanomaterials from the zirconium silicatebased zirconium hydroxide precursors by a precursor-templating method consists of two main steps, namely a) preparing zirconium hydroxide precursors from zirconium silicates: it was started by the decomposition of zirconium silicates with sodium carbonates at 1000 ????C, followed by leaching fired product with water and sulfuric acid, then continued by slow hydrolysis of a zirconium salt solution at approximately pH 9 to obtain zirconium hydroxides; and b) synthesis of onedimensional zirconia nanomaterial from zirconium hydroxide precursors used templates:it was begin with the precursor pH adjustment, followed by mixing the precursors and templates under heating, continued by aging, thus resulting in gels or solids. Then, the original precursors and the as-synthesized products were calcined at 800????C. Both of the produced zirconia characteristics were examined, including thermal behavior, mineralogies, functional groups, microstructures, and textural properties. In this dissertation’s work, one-dimensional zirconia nanomaterials were successfully synthesized from zirconium silicate-based zirconium hydroxide precursors assisted by the selected templates (such as ethylene glycol, poly ethylene glycol 6000, and nano cellulose) and specific synthesis conditions, via a precursortemplating method. The original characteristics of zirconium hydroxide-based zirconia at 800????C include the t-metastable as a dominant phase, particle sizes less than 50 nm, exhibiting a mesopore structure and a surface area of 46.990 m²/g. However, the experimental results show that the usage of one-dimensional directing templates in a precursor-templating method has modified the original characteristics of zirconia, including mineralogies, microstructural and textural properties. The modified zirconias consist of the t-metastable and the m-phases, exhibit one-dimonesional structures (nanorods, nanotubes, nanocapsules, and elongated agglomerates), and reveal surfacea areas in the range 9-48.5 m2/g.